Experimental and numerical study of the hydrodynamic characteristics of a semisubmersible aquaculture facility in waves. (15th October 2020) - Liu, Hang-Fei; Bi, Chun-Wei; Zhao, Yun-Peng
Abstract: Extreme wind and waves can easily destroy aquaculture facilities in the open sea. Therefore, it is essential to analyze the hydrodynamic responses of aquaculture facilities based on a numerical method. To ensure the accuracy of calculation and avoid the huge computational resources required by computational fluid dynamics-CFD, this study adopts a new method that combines the boundary element method based on the potential flow theory with the Morison equation to simulate the hydrodynamic response of a semisubmersible aquaculture facility in pure waves. The hydrodynamic response, including mooring line tension and motion response, is simulated in pure waves and compared with experimental values. The results show that the numerical data agree well with the experimental data. Based on the above work, the numerical model presented here can be used to analyze the hydrodynamic response of a semisubmersible aquaculture facility. The effects of wavelength and wave steepness on the mooring line tension and motion response are studied. Additionally, with increasing draught, both the force on the mooring line and the motion response decrease, and thus, an effective way for an aquaculture facility to avoid damage due to severe waves is through properly increasing draught. Highlights: A new method combines the boundary element method with the Morison equation is applied. Hydrodynamic responses of a semi-submersible aquaculture facility are analyzed. Influence factors including wave steepness, wavelength and draught are analyzed.